Randomised clinical trial: semaglutide versus placebo reduced liver steatosis but not liver stiffness in subjects with non‐alcoholic fatty liver disease assessed by magnetic resonance imaging. Issue 9 (27th September 2021) - Flint, Anne; Andersen, Grit; Hockings, Paul; Johansson, Lars; Morsing, Anni; Sundby Palle, Mads; Vogl, Thomas; Loomba, Rohit; Plum‐Mörschel, Leona
Summary: Background: Glucagon‐like peptide‐1 receptor agonists may be a treatment option in patients with non‐alcoholic fatty liver disease (NAFLD). Aims: To investigate the effects of semaglutide on liver stiffness and liver fat in subjects with NAFLD using non‐invasive magnetic resonance imaging (MRI) methods. Methods: This randomised, double‐blind, placebo‐controlled trial enrolled subjects with liver stiffness 2.50‐4.63 kPa by magnetic resonance elastography (MRE) and liver steatosis ≥10% by MRI proton density fat fraction (MRI‐PDFF). The primary endpoint was change from baseline to week 48 in liver stiffness assessed by MRE. Results: Sixty‐seven subjects were randomised to once‐daily subcutaneous semaglutide 0.4 mg (n = 34) or placebo (n = 33). Change from baseline in liver stiffness was not significantly different between semaglutide and placebo at week 48 (estimated treatment ratio 0.96 (95% CI 0.89, 1.03; P  = 0.2798); significant differences in liver stiffness were not observed at weeks 24 or 72. Reductions in liver steatosis were significantly greater with semaglutide (estimated treatment ratios: 0.70 [0.59, 0.84], P  = 0.0002; 0.47 [0.36, 0.60], P  < 0.0001; and 0.50 [0.39, 0.66], P  < 0.0001) and more subjects achieved a ≥ 30% reduction in liver fat content with semaglutide at weeks 24, 48 and 72, (all P < 0.001). Decreases in liver enzymes, body weight and HbA1c were also observed with semaglutide. Conclusions: The change in liver stiffness in subjects with NAFLD was not significantly different between semaglutide and placebo. However, semaglutide significantly reduced liver steatosis compared with placebo which, together with improvements in liver enzymes and metabolic parameters, suggests a positive impact on disease activity and metabolic profile. ClinicalTrials.gov identifier: NCT03357380. Abstract : In a randomised, double‐blind trial, 67 subjects with NAFLD were randomised to semaglutide 0.4 mg (n = 34) once daily or placebo (n = 33) for 72 weeks. Change in liver stiffness (the primary endpoint) was not significantly different between semaglutide and placebo but liver steatosis, as well as liver enzymes and metabolic parameters, were significantly improved with semaglutide compared with placebo.